ANALISIS OPTIMALISASI BIAYA KUALITAS PADA PT INSPIRA FURNEXINDO - Ayyunda Mahabbah Kasih; Wasti Reviandani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The quality cost is a benchmark for the quality of a wood product who made by PT Inspira Furnexindo. PT Inspira Furnexindo is a company that makes various handicrafts from a quality wood like acacia, rubber wood,mahoni, etc. This study was conducted in order to analyze and determine the use of quality costs in the production process that occurs at PT Inspira Furnexindo, where this type of research is qualitative with a descriptive method. The analysis is carried out by analyzing the quality cost which has not yet been specifically reported by the company. The data collection method used was documentation and interviews which were then analyzed descriptively. The results showed that the analysis of the quality cost at PT Inspira Furnexindo is, thet budge for appraisal costs, prevention costs,, internal and external failure costs have increased every year. however, the percentage of quality costs to sales fluctuated with the highest number of presentations in 2020, then the second highest in 2019 and the smallest in 2021. Quality costs incurred by the company are said to have been optimal as evidenced by an increase in the company's income from the number of product sales.